Physico-chemical properties and sensory of commercial egg tofu - Maizura Murad,; Aminah Abdullah,; Wan Aida Wan Mustapha, (Universiti Kebangsaan Malaysia, 2010)
Analysis on the physico-chemical properties and sensory evaluation of five brands of comercial egg tofu was conducted. The moisture, protein and fat content of the five egg tofu brands were 85.2 – 87.0%, 5.9 – 8.7% dan 3.7 – 4.6%, respectively. The pH value was between 6.2 – 7.1. Results showed that there was no significant different (P>0.05) in sineresis (2.2-2.6%) value was observed for all egg tofu brands. Each brand had significantly different in color lightness in the order: Brand D < Brand A < Brand E < Brand C < Brand B. Brand E egg tofu had the hardess texture which is 31.35 N, meanwhile brand D had the softess texture which is 5.58 N. Results on sensory evaluation obtained clearly showed that the panelists prefer the attribute of appearence, color, aroma, taste, texture (softness) and overall acceptability egg tofu brands A, D and E compared to brands B and C.